AN ANALYSIS OF TYPES OF STUDENTS’ MISBEHAVIORS IN EFL CLASSROOM - Kusuma, Dian Indah; Talib, Ahmad; Farahdiba, Syarifah (JTechLP: Journal of Technology in Language Pedagogy, 2025)
This research was conducted at MTS Guppi Pesuloang, involving 16 seventh-grade students and an English teacher as subjects. This research is a qualitative descriptive study that aims to find out the types of student misbehavior that appear in the EFL class. Student misbehavior as a single variable. This research has two instruments, namely the observation checklist and the interview. From the research it was found that there were 7 misbehaviors committed by students in the process of learning English in the classroom during the research, namely 1) Ignoring the uniform rules, 2) Not paying attention to the teacher's explanation, 3) Distrupting classmates, 4) Using google translate, 5) Diverting the conversation from the subject matter, 6) Disobeying teacher's instructions, and 7) Talking too much.